Comparison of serum testosterone levels in prostate cancer patients - Venkateswaran, Seetha; Margel, David; Yap, Stanley; Hersey, Karen; Yip, Paul; Fleshner, Neil Eric (Canadian Urological Association Journal, 2013)
Introduction: The prostate secretes enzymes and nutrients to promote sperm motility. Recent reports suggest that the prostate may also secrete testosterone, which is believed to be a fuel for prostate tumour growth. The aim of this study was to determine if a difference in serum testosterone levels exists between men on luteinizing hormone releasing-hormone (LHRH) agonists who have undergone radical prostatectomy, radiation or hormone therapy as primary prostate cancer treatment. Methods: Serum testosterone levels were evaluated in 165 consecutive prostate cancer patients using LHRH analogues for >3 months. We excluded patients receiving either radiation or chemotherapy at time of time of testosterone measurement. Patients were classified based on primary treatment: (1) radical prostatectomy; (2) radiation; or (3) primary hormone therapy. We used one-way ANOVA to compare testosterone levels. Pearson correlation was used to correlate testosterone with prostate-specific antigen (PSA) and time on LHRH agonists. Multivariable linear regression was used to predict serum testosterone levels. Results: The median (interquartile range) serum testosterone levels were 1.4 (1-1.9), 1.3 (1-1.625) and 1.25 (0.9-1.525) nmol/L for radical prostatectomy, radiation and primary hormone therapy groups, respectively. There was no statistically significant difference in testosterone levels between the groups (p = 0.3). No correlation was found between testosterone and PSA levels or time on LHRH (r = 0.02 and r = 0.01), respectively. Multivariable linear regression showed that none of the clinical variables were predictors of serum testosterone levels. Conclusion: Our study suggests that primary treatment does not affect serum testosterone levels among men using LHRH analogues.